TRANSLATION STDIES COMPARATIVE LITERATURE AND CONTRASTIVE ANALYSIS - Inog’omjonova Robiya Rustamjon qizi, (Лучшие интеллектуальные исследования, 2023)
In this article, comparative literature and contrastive literature will be discussed, and each of their sections will be discussed. The statement of the opinions of several scientists is also presented in this article. In addition, examples given to each section and necessary and useful points will help you master the above topic well.